Feel First, Buy Later: A Bibliometric Exploration of Emotion-Driven Decision Making in Marketing - Judijanto, Loso (Westscience Press, 2025)
This study presents a bibliometric exploration of emotion-driven decision-making in marketing, aiming to map the intellectual landscape, key contributors, and emerging themes within this growing field. Drawing on a dataset of peer-reviewed articles from the Scopus database (2000–2025), the research employs VOSviewer to visualize co-occurrence networks, author collaborations, institutional linkages, and country-level interactions. The findings highlight “marketing” as the central thematic node, interconnected with clusters such as consumer credit, buy-now-pay-later, customer satisfaction, profitability, and pricing strategy. The overlay and density visualizations reveal a temporal shift from traditional pricing and digital satisfaction metrics toward contemporary issues like financial impulsivity and emotion-triggered consumption. Prominent scholars (e.g., Ailawadi, Ambler), institutions (e.g., University of Oxford), and countries (e.g., United States, United Kingdom) were identified as influential actors shaping the discourse. The study contributes theoretically by bridging emotional, behavioral, and financial dimensions of marketing, while practically guiding marketers to design strategies that align with emotionally charged consumer patterns. Despite limitations in database scope and content depth, this bibliometric analysis offers a foundational platform for future interdisciplinary research on the emotional underpinnings of marketing behavior.